A study on the thermo-mechanical properties of shotcrete structure in a tunnel, excavated in granite at nearly 90 °C temperature. (April 2021) - Hu, Yunpeng; Wang, Qiling; Wang, Mingnian; Liu, Dagang
Abstract: High ground temperature has become a common problem during the development of long, deep and complex geological tunnel. Sangzhuling tunnel is a key program in the construction of Sichuan-Tibet railway in China, where the temperature of surrounding rock reaches 89.9℃, belonging to high ground temperature tunnel. Based on the field test of Sangzhuling tunnel, concrete specimen test cured under high changing temperature and thermal mechanical coupled numerical simulation, a study on the mechanical properties and thermal damage of tunnel shotcrete under high temperature environment was carried out. Analysis of structure revealed that the stress of shotcrete changed rapidly within 10 days, and was basically stable after 18 days. Meanwhile, high temperature intensified the early compressive strength of concrete but it had negative effects on the long-term strength. Furthermore, a numerical model was established to simulate the shotcrete structure. Results of model indicated that the axial force and bending moment of initial support increased with temperature and the lining structure showed a compression failure at 80 ℃ and a tension failure at 60 ℃, especially for spandrel and foot of arch.